Hybridizations within the Genus Schistosoma: implications for evolution, epidemiology and control. Issue 1 (30th August 2016) - LEGER, ELSA; WEBSTER, JOANNE P.
SUMMARY: Hybridization of parasites is an emerging public health concern in our changing world. Hybridization and introgression in parasites and pathogens can have major impacts on the host and the epidemiology and evolution of disease. Schistosomiasis is a Neglected Tropical Disease of profound medical and veterinary importance across many parts of the world, with the greatest human burden within sub-Saharan Africa. Here we review how early phenotypic identification and recent confirmation through molecular studies on naturally occurring infections, combined with experimental manipulations, have revealed evidence of viable hybridization and introgressions within and between human and animal schistosome species. Environmental and anthropogenic changes in selective pressures following, for instance, new dam constructions, altered agricultural practices, together with mass drug administration programmes, may all be predicted to further impact the availability of suitable definitive and intermediate hosts for schistosomes. It is therefore imperative to understand the distribution and role of such novel zoonotic hybrid schistosomes on host range, drug efficacy, and hence ultimately transmission potential, if we are to achieve and maintain sustainable control.